2016
DOI: 10.1021/acs.nanolett.6b01341
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Anomalous Internal Reflections of Hyperbolic Phonon-Polaritons in Hexagonal Boron Nitride

Abstract: We use scanning near-field optical microscopy to study the response of hexagonal boron nitride nanocones at infrared frequencies, where this material behaves as a hyperbolic medium. The obtained images are dominated by a series of "hot" rings that occur on the sloped sidewalls of the nanocones. The ring positions depend on the incident laser frequency and the nanocone shape. Both dependences are consistent with directional propagation of hyperbolic phononpolariton rays that are launched at the edges and zigzag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
113
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 112 publications
(130 citation statements)
references
References 42 publications
(93 reference statements)
12
113
4
Order By: Relevance
“…Inside the h-BN waveguide, we recognize ‘zig-zag' patterns. They manifest HP rays that emerge from corners214647 and reflect at the top and bottom h-BN waveguide surfaces48. As the propagation angle, θ , of the hyperbolic rays depends on the frequency ω (given by21 , the multiple reflections yield complex and frequency-dependent field distributions inside the waveguide, which extend several nanometres above the top waveguide surface.…”
Section: Resultsmentioning
confidence: 99%
“…Inside the h-BN waveguide, we recognize ‘zig-zag' patterns. They manifest HP rays that emerge from corners214647 and reflect at the top and bottom h-BN waveguide surfaces48. As the propagation angle, θ , of the hyperbolic rays depends on the frequency ω (given by21 , the multiple reflections yield complex and frequency-dependent field distributions inside the waveguide, which extend several nanometres above the top waveguide surface.…”
Section: Resultsmentioning
confidence: 99%
“…One broad implication of our work is that nanoimaging of collective modes can reveal nontrivial electron properties, in this case, 1D bound states. Recent experiments have demonstrated that this technique is not limited to plasmons or graphene or 2D systems [27][28][29][30] . We hope that our work stimulates even wider use of this novel spectroscopic tool.…”
mentioning
confidence: 99%
“…Similar to graphene nanoresonators discussed in Section , the localized hyperbolic phonon polariton modes can be excited in patterned polar van der Waals crystals . In patterned h‐BN, hyperspectral resonances with Q‐factors of 283 could be achieved due to the absence of electronic losses in h‐BN .…”
Section: Molecular Sensingmentioning
confidence: 88%